Peningkatan Kualitas Hidup Lansia melalui Cognitive Stimulation Therapy Belajar Membaca Al-Qur’an - Rahmah, Anindita Hasniati; Qoni’ah, Qoni’ah; Dharojah, Rakhma Widya (FORIKES, 2025)
One of the most common health problems in the elderly is impaired cognitive function, a high-level function of the human brain that consists of several aspects, including dementia, which can impact daily activities. The purpose of this study was to explore improving the quality of life of the elderly through the application of cognitive stimulation therapy. This study used a qualitative approach to understand social issues by creating a broad and complex picture, presenting detailed reports from informants, and conducted in a natural setting. Cognitive stimulation therapy was based on religious activities such as reading, memorizing, and listening to Quranic recitations for the elderly with cognitive impairment, particularly dementia. Data were collected through in-depth interviews and then subjected to thematic analysis. The results showed that cognitive stimulation therapy, which involved learning to read the Quran, had an impact on the cognitive domain, namely increased memory related to activities of daily living. This study concluded that cognitive stimulation therapy successfully improved cognitive function, reduced depression, and enhanced quality of life.Keywords: cognitive stimulation therapy; quality of life; elderly; reading the Quran ABSTRAK Salah satu masalah kesehatan yang paling umum terjadi pada lansia adalah gangguan fungsi kognitif yang merupakan fungsi tingkat tinggi otak manusia yang terdiri dari beberapa aspek yaitu demensia, yang bisa berdampak pada aktivitas sehari-hari. Tujuan penelitian ini adalah mengeksplorasi peningkatan kualitas hidup lansia dengan penerapan cognitive stimulation therapy. Penelitian ini menggunakan pendekatan kualitatif untuk memahami masalah sosial dengan membuat gambaran yang luas dan kompleks, menyajikan laporan secara rinci dari informan, dan dilakukan dalam lingkungan alami. Cognitive stimulation therapy berbasis kegiatan keagamaan seperti membaca, menghafal, dan mendengarkan murottal Al-Qur’an pada lansia dengan gangguan fungsi kognitif, khususnya dimensia. Data dikumpulkan melalui wawancara mendalam dan selanjutnya dilakukan analisis tematik. Hasil analisis menunjukkan bahwa cognitive stimulation therapy yang telah dilakukan dengan belajar membaca Al-Quran berdampak pada domain kognitif yaitu terjadi peningkatan daya ingat yang berkaitan dengan aktivitas pada kehidupan sehari-sehari. Penelitian ini menyimpulkan bahwa cognitive stimulation therapy berhasil meningkatkan fungsi kognitif, menurunkan depresi dan meningkatkan kualitas hidup.Kata kunci: cognitive stimulation therapy; kualitas hidup; lansia; membaca Al-Qur’an